Psikologi Kehamilan Dalam Perspektif Al-qur’an - Nurhayati, Eneng (Kopertais Wilayah I DKI Jakarta dan Banten, 2021)
The conclusion from the dissertation is that the psychology of pregnancy in the Qur’an perspective can be understood as a science that studies the behavior of women at the time of pregnancy until birth in building a mentall powers and patterns in harmony with herself, with husband, family member, community, environment and with Allah. In the Qur’an, the psychological discussion of pregnancy covers the turmoil of emotion such as sad, happy. Also, the subject of psychology deals with the senses of the body. Pregnancy psychology, which relates to several biological changes, leads to both intrinsic and extrinsic and the stres due to adjustments to a social pressure. The suppression of stres includes aspects of both the supporting role of the family, and the pregnant women herself, the husband and even the health-care worker. The dissertation also discovered the psychology of pregnancy in the Qur’an, which talks about grief, joy , fear and worry, and so the author found some things related to the psychology of pregnancy in the Qur’an such as: The psychology of the mentally related pregnancy of feelings. The senses and the body, and the mind. And the Desire. This dissertation shares similarity of opinion to Chrissie P, Kaponda. (1996). Descamps, (2014), Deave T, Crowther, Angelica Y. Matos-Rios, (1995) Lori n; Rhodes, Osborne (2001) Nicole Kom-valdina (2012) Jeanne Rodier. Weber (1991). Nasaruddin Umar (2014), M. Darwis Hude, (2006), Nur Arfiyah Pebriani (2014) Fatma syilfana Dewi harahap (2015) who all share the same view that a pregnant woman has an emotional change in the birth of the unborn baby in her womb. The method used in this research is a qualitative and interview method using the maudhu 'i interpretation method. And the data used in this research is obtained through the library research. The steps in this study go through three steps of reading and exploring primary or secondary literature and then analyzing the data with an analistic descriptive framework, ultimately coming to conclusions based on the design and purpose of the research.